2021
DOI: 10.47119/ijrp100771520211932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strategic Leadership on the Performance of Africa Inland Church Theological Training Institutions in Kenya

Abstract: In the recent past, some organizations have either collapsed or are on the verge of collapsing after they had failed to achieve their desired results. The result has been declining financial support, poor utilization of physical resources, and a culture that does not support organizational growth and development. One of the factors that has contributed to the poor performance of these organizations has been lack of strategic leaders. The aim of this study was therefore to determine the effects of strategic lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…However, this study concentrated on tourism-related government agencies rather than county governments, therefore presenting a knowledge gap. Munyao, Chiroma, and Ongeti (2020) carried out research on the relationship between strategic direction and performance in reference to Africa Inland Church in Kenya. Questionnaires with both open-ended and closed-ended questions were used to collect data.…”
Section: Strategic Direction and Operational Efficiencymentioning
confidence: 99%
“…However, this study concentrated on tourism-related government agencies rather than county governments, therefore presenting a knowledge gap. Munyao, Chiroma, and Ongeti (2020) carried out research on the relationship between strategic direction and performance in reference to Africa Inland Church in Kenya. Questionnaires with both open-ended and closed-ended questions were used to collect data.…”
Section: Strategic Direction and Operational Efficiencymentioning
confidence: 99%
“…The results are consistent with the results of past empirical studies. For example, Munyao (2021) indicated that strategic leadership had a positive and significant effect on the performance of Africa Inland Church theological training institutions in Kenya. Likewise, Priadana et al (2021) showed that strategic leadership had a positive and significant effect on business performance in SMEs in Indonesia.…”
Section: Strategic Leadership and Church Growthmentioning
confidence: 99%